CHARACTERIZATION AND SPATIAL DISTRIBUTION OF ACIDIC MINERALS BASED ON PAD 9 WELL IN THE PATUHA GEOTHERMAL FIELD, WEST JAVA: KARAKTERISASI DAN IDENTIFIKASI ZONA PENYEBARAN MINERAL ASAM PADA SUMUR PAD 9 DI LAPANGAN PANAS BUMI PATUHA, JAWA BARAT - Aristo, Muhammad Kurniawan Agung; Suryantini; Idham Andri Kurniawan; Ezidin Reski; Randy Wijaya Atmaja (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Since 2021, PT Geo Dipa Energi has drilled a total of 19 exploration wells to support the development of Patuha Unit-2. Several of these wells are located approximately 1 km from Kawah Putih, an acid vapor core chimney with a pH of less than 2, which has the potential to produce virulent fluids that contribute to the formation of acid-alteration minerals in the wells. This study aims to identify the presence of acid-type minerals, characterize these minerals, estimate their distribution zones, and interpret the formation processes based on data from wells 9-V2 and 9-Z2. The methods employed include modifications to the latest volcanostratigraphic map, macroscopic, microscopic, and XRD analyses of cutting and core samples from wells 9-V2 and 9-Z2, and mineral alteration characterization encompassing alteration type, pattern, intensity, and paragenesis. Well-to-well correlations were established based on spatial position, depth, hydrology, and volcanostratigraphy. The updated volcanostratigraphic map identifies 12 volcanic units (11 domes and 1 maar), with Kawah Putih representing the youngest unit. Identified acid-type minerals include anhydrite and diaspore. The formation of these minerals occurs through direct precipitation and replacement processes, with moderate to strong alteration intensity. Acid mineral formation is overprinted by later alteration under more neutral pH conditions. In the well group 9, the formation of acid-type minerals is interpreted to result from the lateral mixing of virulent fluids with shallow groundwater. This mixing process is characterized by the presence of calcite and other minerals enriched in Mg.